Cognitive style of a future IT specialist in a teamwork process - N. V. Buzhinskaya; E. S. Vaseva; I. E. Shkabara (Russian State Vocational Pedagogical University, 2022)
Introduction. Training future specialists in information technology to work in a team has a great potential both for solving educational problems in the higher education and for further development of graduates as professionals in the labour market. The efficiency of the teamwork is largely determined by the effectiveness of the distribution of roles in the team. The distribution of roles depends on the individual cognitive characteristics of each team member. Individual enlightening characteristics of the ways of perception and processing of information, the choice of ways to solve problems are associated with the cognitive style of the individual.Aim. The present research aims to analyse the nature of the influence of the cognitive style of the personality of each member of the team on the results of solving a practice-oriented task in the field of information and communication technologies.Methodology and research methods. The work used a systematic approach (N. A. Astashova, S. L. Melnikova, A. P. Tonkikh, L. N. Shilenkova, A. Burger, L. Naude, F. D. Fernandez, J. L. Arco-Tirado, M. Hervas-Torres); practice-oriented approach (E. F. Fefilova, D. Bednarek, M. Krulis, J. Yaghob); project approach (L. I. Savva, E. A. Gasanenko, K. E. Shakhmaeva); cognitive approach (J. B. Watson, G. A. Kimble, J. Anderson, B. M. Velichkovsky, J. Kelly, J. Bruner, J. J. Goodnow, G. A. Austin, M. A. Kholodnaya), in the frames of which general scientific and statistical methods were used. The works by M. A. Kholodnaya, J. Parker, J. D. Bain, H. A. Witkin, S. A. Moore, D. R. Goodenough, P. W. Cox constituted the theoretical and methodological basis of the study, on the basis of which the characteristics of students with different cognitive styles were studied. The analysis of the dependence of the success rate of solving practice-oriented tasks by a team of students on the cognitive style of each member of this team was carried out. The success rate was calculated as the sum of the normalised values for each type of work. 250 undergraduate students of Nizhny Tagil State Socio-Pedagogical Institute (branch) of Russian State Vocational Pedagogical University and Nizhny Tagil Institute of Technology (branch) of Ural Federal University took part in the study. The used research methods: questionnaires, testing, the method of expert assessments, ranking, scaling, rationing, content analysis of documents, methods of mathematical statistics in data processing, methods of analysis, synthesis, generalisation, comparison, abstraction when interpreting research results. The "Included Figures" test was used to determine the field dependence / field independence of the subjects. The main statistical calculations were performed using the nonparametric statistical method "Mann-Whitney U-test". To confirm the reliable difference in the proportion of teams that successfully coped with the task, the Fisher criterion was applied. The data sources are open source databases (websites of international and Russian government bodies), regulatory documents regulating the basics of training IT specialists, research by leading scientists in the field of cognitive personality style, statistical information.Results. The authors developed the criteria to evaluate the results of solving a practiceoriented task by a team of future IT specialists and defined the concept of a success indicator. The authors demonstrated the importance of taking into account cognitive personality styles when forming a team of IT specialists. The dependence of the success rate of solving a practice-oriented task on the type of cognitive style of the participants of the task was revealed. It is established that the highest results of the success rate in solving a practice-oriented task were noted in those teams that included students with different cognitive personality styles of field dependence / field independence, with a predominant number of participants with a field-independent personality style. The findings indicate the need to take into account the cognitive styles of individuals when forming the composition of teams for IT projects.Scientific novelty. The results of the study expand the scientific facts that cognitive styles are predictors of students' achievements in solving practical tasks in teamwork.Practical significance. The data obtained can be used to develop a strategy for training future IT specialists aimed at improving the effectiveness of teamwork in higher education institutions. The proposed calculations of the success rate of solving practice-oriented tasks can be employed to evaluate the results of educational practices and final qualifying works.